Pengaruh Aditif Metanol Dan Ketebalan Membran Terhadap Karakteristik Membran Berbasis Selulosa Asetat - Gemilang, Evrina Cahya; Zulkaisi; Susilowati; Nurherdiana, Silvana Dwi (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Membrane technology is a process capable of separating chemical species from a feed solution to produce permeate. In membrane fabrication, cellulose acetate polymer is commonly used due to its ability to form asymmetric membrane structures. Additives can be used to modify membrane morphology, especially pore formation. Methanol's high solubility in non-aqueous solvents makes it an efficient pore development additive. Membrane thickness affects membrane properties, particularly permeability. This study will look into how methanol additions and membrane thickness affect the properties of cellulose acetate-based membranes. The membranes were fabricated using the phase inversion method with methanol concentrations of (2, 4, 6, 8, and 10%) and membrane thicknesses of (100, 200, 300, 400, and 500 µm), employing N-Methyl Pyrrolidone (NMP) as the solvent and aquadest as the non-solvent. Characterization of the membranes involved contact angle analysis, porosity, water flux, and Scanning Electron Microscopy (SEM). The results revealed that the membranes were hydrophilic, with contact angle readings less than 90 degrees. The ideal membrane, with a thickness of 100 µm, a porosity value of 87.821%, and a water flux value of 363.967 L/m2 hour.